The effect of yogic training and aerobic training on selected managerial mood : states among women university players - Narayanan, R. (university of Jaffna, 2014)
Forty five women players were selected as subjects at random from Department of Physical Education Women University Players, Annamalai University at chidambaram and their age was 18-25 years. They were divided in to three groups such as Control, Yogic Training, Aerobic Training groups prior to the experiment, all the subjects were medically tested and found physically fit. In this article here only one variable was selected, Dependent Variable: Managerial Mood states- Mc Nair Questionnaire tool was evaluated the players Managerialmood states. Analysis of Covariance statistics technique was used to analyse the main and interaction effects of study. There was significant difference in the Effect of Yogic Training and Aerobic Training among Women University players.
Keywords: Yogic training; Aerobic training